TO DETERMINE THE SURVIVAL OF PATIENTS WITH BRAIN METASTASES AFTER PALLIATIVE WHOLE-BRAIN RADIOTHERAPY - AN EXPERIENCE FROM A SINGLE INSTITUTE - Misbah, Dawood; Muhammad Fawad-Ul-Qamar; Khaleeq, Nadia; Zaidi, Alina; Ali Shah, Syed Zarak; Sajjad, Kashif (Journal of Ayub Medical College Abbottabad, 2023)
Background: Brain metastases are a common complication of cancer and approximately 20% of cancer patients develop them over time. Presently palliative whole-brain radiotherapy is used as a palliative treatment for brain metastases because of its cost-effectiveness and easy availability, especially in patients with multiple metastases who are not candidates for surgery or Stereotactic radiosurgery. This study aims to determine the survival in patients who have received palliative whole-brain radiotherapy for brain metastases and to evaluate some of the prognostic factors determining survival in patients with brain metastases. Methods: It was a cross-sectional study conducted in Shaukat Khanum Memorial Cancer Hospital and Research Centre and all the patients with brain metastases who had completed palliative whole-brain radiotherapy between July 2015 and July 2020 were included. Data was retrospectively collected and analyzed using SPSS 21.0. Overall survival was calculated using the Kaplan-Meier method, taking into consideration the period from the date of diagnosis of brain metastases until death or to the date of last follow-up, whichever was applicable. p-value of <0.05 was regarded as statistically significant. Results: Almost half (45%) of the brain metastases were secondary to breast cancer followed by lung and genitourinary cancers at 16.3% and 15.5% respectively. The median overall survival was lowest in breast carcinoma patients at 5 months followed by lung carcinoma at 7 months. The median overall survival was 5 months in patients having extracranial disease as compared to 12 months in those having no extracranial disease or those in whom the disease status was unknown. Conclusions: Our study revealed that the most common tumour to metastasize to the brain was breast cancer. The younger age group had a poorer prognosis because most of them had breast cancer with triple-negative disease. Controlled extracranial disease significantly prolonged overall survival in patients with brain metastases.